Analisis Kepuasan Pelanggan dengan Metode Service Quality (Servqual) dan Importance Performance Analysis (IPA) pada UMKM Gabin Osing di Banyuwangi - Marafi, Ghaly Insan; Suprihatin, Endang; Hidayah, Asfarina (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Gabin Osing is a snack business line located in Banyuwangi. The aim of conducting this research is to determine customer preferences using the service quality (servqual) and importance performance analysis (IPA) methods. The research results found that the cause of the decline in customer satisfaction by analyzing the service quality method was the need to prioritize improvements to the Gabin Osing product, namely in the dimensions of feature, reliability, conformance and durability. Meanwhile, the factors that have a low level of satisfaction and a high level of importance using the importance performance analysis method occupy quadrant A, namely in the statement of benefits when consuming the Gabin Osing product, namely how important it is for the Gabin Osing product to fulfill nutrition; how important it is for Gabin Osing products to meet nutritional value; how important the Gabin Osing product is in curbing hunger; and how important it is for Gabin Osing products to fulfill the taste image when consumed.